Pengaruh Kualitas Produk dan Persepsi Harga Terhadap Kepuasan Pelanggan dan Dampaknya Pada Minat Beli Ulang : Studi pada Konsumen Skincare Hanasui - Vika Nafia Zakiana; Alimuddin Rizal Rivai (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to test and analyze the effect of product quality and price perceptions on customer satisfaction and its impact on repurchase interest using quantitative data where the results of this study will be in the form of numbers processed using IBM SPSS 22 software. The population in this study are consumers of Hanasui skincare products and have the intention to repurchase Hanasui skincare products. The sampling method in this study uses non-probability sampling with purposive sampling technique where the sample is taken based on certain criteria. The data collection method used is a questionnaire with a Likert measurement scale of 1 - 7, so that the data obtained is 100 respondents. Data analysis in this study used multiple linear regression. The results showed that product quality has a positive and significant effect on customer satisfaction, price perception has a positive and significant effect on customer satisfaction and customer satisfaction has a positive and significant effect on repurchase intention.